The Cost of a Counseling-Based Intervention for Moderate Acute Malnutrition (MAM) in Kenya Compared to Treatment with Ready-to-Use Foods (RUF). (29th May 2020) - Wright, Charlotte; Mutoro, Antonina; Grieve, Eleanor; Garcia, Ada; Donfouet, Hermann P; Kimani-Murage, Elizabeth
Abstract: Objectives: Supplementary feeding with RUF is currently the recommended treatment for MAM in Kenya, although trials suggest it produces only modest medium-term benefits. An alternative counseling-based approach which identified and addressed the varied underlying causes for MAM would involve increased staff time. In order to model the future cost of providing a targeted, problem solving intervention for MAM instead of supplementary foods, we aimed to estimate the current staff and facility cost of managing acute malnutrition using RUF. Methods: We studied 6 health facilities in Nairobi, Kenya in 2019, assessing the amount of staff time spent in treatment of AM and managing RUF supplies, via interview and observation. Information was collected on: time spent per child per visit, number of children with AM seen by nutritionists annually, time spent by staff per year on requisition and management of RUF and in relevant training, staff wage rates and RUF transport costs. Costs were calculated in US, per child/month, assuming each child was seen once and supplied with 28 RUF sachets. Results: Centers saw 7–80 children per clinic and staff spent 5–9 minute seeing each child. The contact cost per child visit was 0.14–0.25 and the dispensing cost 0.02–0.34, giving a mean (range) total cost of 0.24 (0.17 – 0.59). The hourly pay for nutritionists was 1.67. The exact cost of RUF varies, depending on supplier and purchaser, but was estimated to vary from 0.25 to 0.50 per sachet, giving a monthly cost of 7–14. This represents 96–98% of total current MAM treatment costs. Conclusions: Very little time is currently spent speaking to mothers of malnourished children. An intervention for MAM could involve up to 8 hours counseling per month per child and still be cheaper to provide than supplementary RUTF. Well-staffed trials of the efficacy of problem-oriented counseling interventions need to be undertaken. Funding Sources: Scottish Funding Council (Global Challenges Research Fund).